Milk stage kernel infection frequency and its relationship with grain mold development in sorghum - Das, I K; Govardhan, C; Patil, J V (Indian Journal of Plant Protection, 2020)
Field experiments were conducted with four popular grain sorghum cultivars that included two varieties and two hybrids during two successive rainy seasons 2012 and 2013 at Hyderabad to quantify natural infection at milk stage kernel of popular sorghum cultivars and lists fungal genera associated with it. Further, the role of early seed infection on grain mold severity was decided. The study reports natural frequency of fungal infection and fungal diversity at milk stage kernel of sorghum. Frequency of natural infection was about 25%. Four different fungal genera were recovered from milk stage kernel. The genus Fusarium was major (18%) fungus followed by Curvularia (5%), Alternaria (1.3%) and Bipolaris spp. (0.9%). This report shows quantification of infection of various fungi on milk stage sorghum grain. Frequency of early infection played significant role in deciding grain mold severity on post-maturity sorghum.